An enhanced burst assembly scheme over optical burst switching networks. (2017) - Al-Shargabi, Mohammed; Saeed, Faisal; Ismail, Abdul Samad; Idrus, Sevia M.
Recently, real-time traffic occupied a large portion of the internet's traffic, which has strict quality of service (QoS) requirements in terms of delay. Thus, guaranteeing the network end-to-end delay is one of the main important factors to guarantee the QoS for the real time traffic over the internet. Constant bit rate (CBR) traffic is one of the real time traffic forms that have been proposed as a solution for reducing the size of transmission and storage. In optical burst switching (OBS) network, the entire delay is calculated based on the collection of the burst assembly time, the offset time, and the propagation delay. Thus, the OBS must be able to guarantee the delay requirements of CBR traffic as real time traffic. This paper introduces a novel OBS burst assembly scheme called burst assembly with CBR traffic delay requirements (BACDR) scheme that guarantees the delay requirements of CBR traffic over OBS networks. The results showed that the BACDR scheme can guarantee the delay requirements of CBR traffic under various conditions such traffic load, the value of maximum packet transfer delay, or the design of the network topology.